Titanium dioxide and gold nanoparticles toxicity in albino rats: Biochemical, anatomical, histopathological, and immunohistochemical studies - Yasmine A. Mansour; Alaa H. Elsayed; Fady Sayed Youssef; Sameh H. Ismail; Gehad Genidy Mohamed; Meray N. Ramsis; Samar Kamel; Basma A. Elkhadrawey; Mujtaba Farooq Rana; Heba H. Mahboub; Aya M. Mekkawy (Tissue and Cell, 2027)

Comparative assessment of cerium hydroxide- and cerium oxide-modified biochar for phosphate remediation from food industry wastewater - Muwaffaq Imran Mohammed; Lubna Jaber; Alaa Abushawish; Ismail W. Almanassra; Omar Awayssa; Tahar Laoui; Muataz Ali Atieh (Biomass and Bioenergy, 2027)

Upcycling date palm petiole for sustainable solar-driven interfacial evaporation - Maryam Nooman AlMallahi; Alaa Abushawish; Ismail W. Almanassra; Omar Awayssa; Muataz Ali Atieh; Mohamed Y.E. Selim; Mahmoud Elgendi (Biomass and Bioenergy, 2026)

Valorization of olive pomace into gadolinium-modified biochar for phosphate removal from wastewater - Alaa Abushawish; Ismail W. Almanassra; Lubna Jaber; Haif Aljomard; Muataz Ali Atieh; Omar Awayssa (Biomass and Bioenergy, 2026)

Comparative analysis of the morphological heterogeneity of smooth muscle cells in two avian species: the muscovy Duck (Cairina moschata) and the Japanese quail (Coturnix japonica): ultrastructural and histochemical study - Hanan H. Abd-Elhafeez; Alaa Sayed Abou-Elhamd; Basma Mohamed Kamal; Hesham Ismail; Sherief M. Abdel-Raheem; Mahmoud H. A. Mohamed; Ahmed M. A. Meligy; Soha A. Soliman (Protoplasma, 2026)

Response to “Critical evaluation of ‘efficacy and safety of esketamine for sedation during colonoscopy: a systematic review and meta-analysis of randomized controlled trials - Zainab Hussein; Amira Mohamed Taha; Alaa Abdrabou Abouelmagd; Mohamed Nasser Elshabrawi; Abdul Karim Durvesh; Eman Ayman Nada; Mohamed Abuelazm; Mohamed Elnaggar; Ismail Elkhattib (European Journal of Clinical Pharmacology, 2026)

The potential role of adenosinergic pathway and methylxanthines in Parkinson’s disease: Blowing in the wind or not - Alaa Ismail; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Ali K. Albuhadily; Luay M. Alkazmi; Abdullah Faisal Albukhari; Mustafa M. Shokr; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Purinergic Signalling, 2026)

Efficacy and safety of esketamine for sedation during colonoscopy: A systematic review and Meta-analysis of randomized controlled trials - Zainab Hussein; Amira Mohamed Taha; Alaa Abdrabou Abouelmagd; Mohamed Nasser Elshabrawi; Abdul Karim Durvesh; Eman Ayman Nada; Mohamed Abuelazm; Mohamed Elnaggar; Ismail Elkhattib (European Journal of Clinical Pharmacology, 2026)
Background Hemodynamic instability during colonoscopy sedation remains a significant clinical concern. Esketamine’s sympathomimetic properties may protect against these risks while reducing sedative requirements. Hence, we aim to evaluate the efficacy and safety of esketamine in improving intraprocedural sedation during colonoscopy. Methods We systematically searched PubMed, Scopus, CENTRAL, and Web of Science until June 2025 for randomized controlled trials. The primary outcome was the incidence of intraprocedural hypotension; secondary outcomes included bradycardia, hypoxemia, and recovery parameters. Dichotomous outcomes were pooled using risk ratios (RR) and continuous outcomes using standardized mean differences (SMD), with heterogeneity assessed via I² statistics. PROSPERO ID: CRD420251105691. Results Five randomized controlled trials comprising 858 patients were included in our analysis. Esketamine significantly reduced the risk of intraprocedural hypotension (RR: 0.34, 95% CI 0.22–0.53; I²=58%) and the incidence of hypoxemia (RR: 0.38, 95% CI 0.19–0.73; I²=0%). A reduction in injection pain was also observed (RR: 0.42, 95% CI 0.19–0.97; I²=80.5%), though this finding showed sensitivity in leave-one-out analysis. No significant differences were found between groups in bradycardia risk (RR: 0.51, 95% CI 0.23–1.14), total propofol requirement (SMD: -0.23, 95% CI -0.50 to 0.04), induction time, or procedure duration. The reduction in hypotension remained robust in sensitivity analyses. Conclusion Esketamine significantly enhanced hemodynamic stability and reduced sedative demand during colonoscopy without delaying recovery, supporting its use in high-risk patients.

Tailored olive pomace biochar anchored with CaAl layered double oxides for phosphate remediation from food industry wastewater: Role of pyrolysis and mechanistic insights - Alaa Abushawish; Ismail W. Almanassra; Muataz Ali Atieh; Omar Awayssa (Journal of Water Process Engineering, 2026)

Unveiling the Neuroprotective Effect of Paraoxonase 1 in Neurodegenerative Diseases Focusing on Alzheimer’s Disease - Alaa Ismail; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Athanasios Alexiou; Marios Papadakis; Safaa A. Faheem; Gaber El-Saber Batiha (Molecular Neurobiology, 2026)

Interconnection between myasthenia gravis and type 2 diabetes: emerging role of metformin in modulating PI3K/AKT/mTOR/AMPK axis - Ahmed salem Al-Dhahi; Hayder M. Al-Kuraishy; Ali I. Al-Gareeb; Ali K. Albuhadily; Aya M. Mustafa; Alaa Ismail; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Metabolic Brain Disease, 2025)

The protective effect of Adansonia digitata fruit extract against severe heat stress on growth performance, feed efficiency, and health status of fattened rabbits - Rehab F. S. A. Ismail; Mahmoud A. E. Hassan; Sahar R. M. Hammoudah; Mona A. Ragab; Abdelhamid M. Abdelhamid; Alaa M. A. Gad (Tropical Animal Health and Production, 2025)

Influence of pyrolysis temperature on pistachio shell biochar for enhanced PFOA removal from wastewater: A sustainable approach to PFAS remediation - Maha Abu Mahfoud; Lubna Jaber; Ismail W. Almanassra; Alaa Abushawish; Muath Mousa; Muataz Ali Atieh (Journal of Water Process Engineering, 2025)

Perichondral telocytes and their role in cartilage development and regeneration: Insights from histochemistry, immunohistochemistry, and TEM - Hanan H. Abd-Elhafeez; Alaa Sayed Abou-Elhamd; Hesham Ismail; Sherief M. Abdel-Raheem; Ahmed M.A. Meligy; Soha A. Soliman (Research in Veterinary Science, 2025)

High-resolution sequence stratigraphy and microfacies analysis of the lower part of the Sa'di Formation in selected wells from the West Qurna oilfield, southern Iraq - Maher J. Ismail; Maher M. Mahdi; Frank R. Ettensohn; Rafea A. Abdullah; Amna M. Handhal; Alaa M. Al-Abadi (Journal of African Earth Sciences, 2025)

APTES-functionalized MoS2@ZnO nanocomposite for ultrafiltration: Advanced characterization and oil/water separation performance - Lubna Jaber; Alaa Abushawish; Omar Awayssa; Abdallah Shanableh; Muataz Ali Atieh; Ismail W. Almanassra (Chemical Engineering Journal, 2025)

Synthetic shale gas produced water pre-treatment via ultrafiltration membranes enhanced with polydopamine-coated hydroxylated 2D boron nitride nanosheets - Ismail W. Almanassra; Alaa Abushawish; Lubna Jaber; Omar Awayssa; Abdallah Shanableh; Muataz Ali Atieh; Roqaya A. Ismail (Desalination, 2025)

Gold nanoparticles mediate suppression of angiogenesis and breast cancer growth via MMP-9/NF-κB/mTOR and PD-L1/PD-1 signaling: integrative in vitro validation and network pharmacology insights - Alaa Elmetwalli; Tarek El-Sewedy; Mervat G. Hassan; Mohamed O. Abdel-Monem; Jihan Hassan; Nadia F. Ismail; Afrah Fatthi Salama; Junjiang Fu; Nasser Mousa; Deema Kamal Sabir; Ola El-Emam; Ghada Hamdy; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Geochemistry of the U-bearing lithofacies within the major graben in Um Bogma area, Sinai, Egypt: implications for mineralization genesis and controlling factors - Ahmed E. Shata; Alaa Mostafa; Mahmoud M. Nasr; Ahmed M. Ismail; Hesham S. Serag El Din (Carbonates and Evaporites, 2025)

Successful preparation of CeO2-modified 2D boron nitride for enhanced dye and humic acid separation with ultrafiltration membranes - Lubna Jaber; Alaa Abushawish; Yehia Manawi; Abdallah Shanableh; Muataz Ali Atieh; Mathias Ulbricht; Ismail W. Almanassra (Journal of Water Process Engineering, 2024)

Macadamia nut shell biochar/Mg-Al LDH composite: A sustainable solution for highly effective phosphate ion removal from water - I. Ihsanullah; Ismail W. Almanassra; Alaa Abushawish (Journal of Water Process Engineering, 2024)

Coupling of a streamlined solid-liquid extraction protocol with LC-ESI-MS/MS for the regular oversight of illegal bromate additive use: An accurate and sensitive determination method in preliminary and bakery products - Amira A. Abdulrahman El-Bahar; Amr H. Shendy; Alaa El-Dean Fathy Ahmed Aboalhassen; Ahmed M. Gomaa; Eman H. Ismail (Food Chemistry, 2024)

Plasmonic titanium nitride-based membranes for solar-driven domestic wastewater distillation treatment - Aya Ghazal; Alaa Shaheen; Sarah AlBlooshi; Meera Almehrzi; Roqaya A. Ismail; Nahla AlAmoodi; Seunghyun Hong; Faisal AlMarzooqi (Chemical Engineering Journal, 2024)

Potentially Toxic Element (PTE) Sources in the Middle Eocene Carbonate Aquifer, East El Minia, Egypt - Abdel-Aziz A. Abdel-Aziz; Salman A. Salman; Esam A. Ismail; Alaa Mostafa; Ramadan S. A. Mohamed (Water, Air, & Soil Pollution, 2024)
Water pollution with potentially toxic elements (PTEs) becomes a major threat to the validity of that water for drinking and agriculture and hence human life. The current study aims to evaluate the carbonate aquifer groundwater PTE content, sources, and impact on water quality. To achieve this goal, drilling cutoff of two wells and 30 groundwater samples were collected and chemically analyzed. The groundwater has TDS values ranged from 271.2 to 971.8 mg/l. Freshwater recharge process led to the continuous freshening of the aquifer and enhanced the forward ion exchange reactions. Carbonate and evaporate mineral dissolution/precipitation processes are the main controller of groundwater chemistry. Cd and As represented the most hazardous elements in these rocks followed by Pb. The presence of high concentrations of PTEs (As, Cd, Cr, and Pb) in water-bearing carbonate rocks has led to detritus of water quality and its unsuitability for drinking owing to the occurrence of these harmful elements in water. Even though the high concentrations of PTEs in the studied water, these elements occurred in low mobility and toxicity species: Fe(OH) 3 , Mn 2+ , (HAsO 4 ) −2 , Cd 2+ , Cr 2 O 3 , Cu 2 O, CuO, and PbCO 3 . This reflects the importance of studying element species rather than total concentration. Even though the unsuitability of this water for drinking owing to high concentrations of some PTEs, all of the samples were found to be suitable for irrigation.

Perceptions of medicinal herbal products during the COVID-19 pandemic period among Saudi patients: a cross-sectional study - Aisha Nawaf Al balawi; Alaa R. El-Alosey; Jayda G. Eldiasty; Ismail Y. H. Abushalfeh; Angod Ahmed Almasaude; Sahar Abd-El Razik Mosallam; Alaa Elmetwalli (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Novel composites of activated carbon and layered double oxide for the removal of sulfate from synthetic and brackish groundwater - Alaa Abushawish; Anjaneyulu Chatla; Ismail W. Almanassra; I. Ihsanullah; Abdallah Shanableh; Tahar Laoui; Muataz Ali Atieh (Chemosphere, 2023)

Relationship between structural style and the petroleum system in the siba gas field, southern Iraq - Amna M. Handhal; Mohammed Q. Aljazaeri; Wathiq Abdulnaby; Frank R. Ettensohn; Alaa M. Al-Abadi; Maher J. Ismail (Marine and Petroleum Geology, 2023)

Unveiling the relationship between MOF porosity, particle size, and polyethersulfone membranes properties for efficient decontamination of dye and organic matter - Ismail W. Almanassra; Lubna Jaber; Anjaneyulu Chatla; Alaa Abushawish; Abdallah Shanableh; Muataz Ali Atieh (Chemical Engineering Journal, 2023)

Sulphate removal from aqueous solutions: State-of-the-art technologies and future research trends - Anjaneyulu Chatla; Ismail W. Almanassra; Alaa Abushawish; Tahar Laoui; Hussain Alawadhi; Muataz Ali Atieh; Noreddine Ghaffour (Desalination, 2023)

Hematological consequences of polyethylene microplastics toxicity in male rats: Oxidative stress, genetic, and epigenetic links - Amina A. Farag; Heba S. Youssef; Rania E. Sliem; Walaa Bayoumie El Gazzar; Nashwa Nabil; Maha M. Mokhtar; Yasmin M. Marei; Nesma S. Ismail; Shaimaa E. Radwaan; Amira M. Badr; Alaa El-Din Hamid Sayed (Toxicology, 2023)

Evaluation of the therapeutic potential of cerebrolysin and/or lithium in the male Wistar rat model of Parkinson’s disease induced by reserpine - Engy K. Tharwat; Ahmed O. Abdelaty; Alaa I. Abdelrahman; Hebatallah Elsaeed; Ayatallah Elgohary; Amena S. El-Feky; Yasmina M. Ebrahim; Alaa Sakraan; Hossam A. Ismail; Yasser A. Khadrawy; Heba S. Aboul Ezz; Neveen A. Noor; et al. (Metabolic Brain Disease, 2023)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disease worldwide and represents a challenge for clinicians. The present study aims to investigate the effects of cerebrolysin and/or lithium on the behavioral, neurochemical and histopathological alterations induced by reserpine as a model of PD. The rats were divided into control and reserpine-induced PD model groups. The model animals were further divided into four subgroups: rat PD model, rat PD model treated with cerebrolysin, rat PD model treated with lithium and rat PD model treated with a combination of cerebrolysin and lithium. Treatment with cerebrolysin and/or lithium ameliorated most of the alterations in oxidative stress parameters, acetylcholinesterase and monoamines in the striatum and midbrain of reserpine-induced PD model. It also ameliorated the changes in nuclear factor-kappa and improved the histopathological picture induced by reserpine. It could be suggested that cerebrolysin and/or lithium showed promising therapeutic potential against the variations induced in the reserpine model of PD. However, the ameliorating effects of lithium on the neurochemical, histopathological and behavioral alterations induced by reserpine were more prominent than those of cerebrolysin alone or combined with lithium. It can be concluded that the antioxidant and anti-inflammatory effects of both drugs played a significant role in their therapeutic potency.

Impacts of microplastics on reproductive performance of male tilapia (Oreochromis niloticus) pre-fed on Amphora coffeaeformis - Rania F. Ismail; Norhan E. Saleh; Alaa El-Din H. Sayed (Environmental Science and Pollution Research, 2021)

Nanoparticles functionalized ceramic membranes: fabrication, surface modification, and performance - Dina Ewis; Norhan Ashraf Ismail; MhdAmmar Hafiz; Abdelbaki Benamor; Alaa H. Hawari (Environmental Science and Pollution Research, 2021)

Formulation and Characterization of Nanosized Ethosomal Formulations of Antigout Model Drug (Febuxostat) Prepared by Cold Method: In Vitro/Ex Vivo and In Vivo Assessment - Ahmed A. El-Shenawy; Wael A. Abdelhafez; Ahmed Ismail; Alaa A. Kassem (AAPS PharmSciTech, 2020)

Expanding the spectrum of germline variants in cancer - Abdul K. Siraj; Tariq Masoodi; Rong Bu; Sandeep Kumar Parvathareddy; Ismail A. Al-Badawi; Nasser Al-Sanea; Luai H. Ashari; Alaa Abduljabbar; Samar Alhomoud; Saif S. Al-Sobhi; Asma Tulbah; Dahish Ajarim; et al. (Human Genetics, 2017)

Endocrine disruption, oxidative stress, and testicular damage induced by 4-nonylphenol in Clarias gariepinus: the protective role of Cydonia oblonga - Alaa El-Din H. Sayed; Rania F. K. Ismail (Fish Physiology and Biochemistry, 2017)

Molecular-Level Characterization of Normal, Benign, and Malignant Breast Tissues Using FTIR Spectroscopy - Wael M. Elshemey; Alaa M. Ismail; Nihal S. Elbialy (Journal of Medical and Biological Engineering, 2016)

Assessment and characterization of ambient indoor particulate matters using aerosol monitor, inductively coupled plasma mass spectrometry, and transmission electron microscopy - Alaa A. Salem; Ismail A. El-Haty; Mohamed Al-Gunaid; Mahmoud Al-Balushi; Bashar Y. Abu-Hattab; Anas Al-Aidros; George O. Odhiambo (Air Quality, Atmosphere & Health, 2015)

Determination of nitrogen dioxide, sulfur dioxide, ozone, and ammonia in ambient air using the passive sampling method associated with ion chromatographic and potentiometric analyses - Alaa A. Salem; Ahmed A. Soliman; Ismail A. El-Haty (Air Quality, Atmosphere & Health, 2009)

The changing patterns of bladder cancer in Egypt over the past 26 years - Ashley S. Felix; Amr S. Soliman; Hussein Khaled; Mohamed S. Zaghloul; Mousumi Banerjee; Manal El-Baradie; Mohamed El-Kalawy; Alaa A. Abd-Elsayed; Kadry Ismail; Ahmed Hablas; Ibrahim A. Seifeldin; Mohamed Ramadan; et al. (Cancer Causes & Control, 2008)